2004
DOI: 10.1063/1.1767282
|View full text |Cite
|
Sign up to set email alerts
|

Mobility studies of field-effect transistor structures basedon anthracene single crystals

Abstract: The charge carrier transport in anthracene single crystals has been studied by means of field-effect transistor (FET) structure. The FET mobility (μFET) revealed the nonmonotonous, reliant on gate-voltage (Vg), temperature dependence with the maximum μFET∼0.02cm2∕Vs at T∼170–180K and Vg∼−30V. At temperatures below 180K the mobility decreases and becomes thermally activated with the Vg-dependent activation energy Ea∼40–70meV governed by shallow traps. The space-charge-limited current is the dominant transport m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
101
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(108 citation statements)
references
References 18 publications
6
101
1
Order By: Relevance
“…Such technique uses the ability of thin, usually 1 mm or thinner, and flat organic crystals to adhere to other even surfaces, metallic or insulators, by electrostatic forces and to other organic material layers, such as SAMs 25 or polymers (for example, polymethylmethacrylate 26 ). Examples arrive from different classes of molecular materials, such as the acenes [25][26][27][28] , metal phtalocyanines 29 , thiophenes 30 or the fulvalenes 31 . As long as the substrate roughness is smaller than just a few nanometres, thin organic crystals are flexible enough to adjust to most substrate surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…Such technique uses the ability of thin, usually 1 mm or thinner, and flat organic crystals to adhere to other even surfaces, metallic or insulators, by electrostatic forces and to other organic material layers, such as SAMs 25 or polymers (for example, polymethylmethacrylate 26 ). Examples arrive from different classes of molecular materials, such as the acenes [25][26][27][28] , metal phtalocyanines 29 , thiophenes 30 or the fulvalenes 31 . As long as the substrate roughness is smaller than just a few nanometres, thin organic crystals are flexible enough to adjust to most substrate surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…This I-V behavior is similar to previous results for anthracene single crystals where SCLC transport is thought to be the predominant transport mechanism. [23,24] As a more negative V GS is applied, more holes are induced in the semiconductor and the conductance of the channel region increases. A strong field-effect modulation of the channel conductance and current levels as high as 25 lA have been observed, as shown in Figure 4A.…”
mentioning
confidence: 99%
“…However, even in the best organic TFTs, charge transport is still dominated by the presence of structural defects and chemical impurities. As a result, it has been concluded that the TFTs "may not be appropriate vehicles for illuminating basic transport mechanisms in organic materials " ͑Nel-son et al, 1998͒. Recently developed single-crystal organic transistors with significantly reduced disorder ͑Butko et al, 2003;de Boer et al, 2003;Podzorov, Sysoev, et al, 2003;Takeya et al, 2003;Aleshin et al, 2004;de Boer, Gershenson, et al, 2004;Sundar et al, 2004͒ provide unique opportunities to explore fundamental processes that determine operation and reliability of organic electronic devices. For the first time, these single-crystal OFETs have enabled the observation of intrinsic ͑not limited by static disorder͒ transport of field-induced charges on organic surfaces ͑Menard et Podzorov, Menard, Borissov, et al, 2004;.…”
Section: Introduction: Field Effect In Small-molecule Organic Semimentioning
confidence: 99%